Gender Differences in Risk Factors for Adolescent Binge Drinking and Implications for Intervention and Prevention - Dir, Allyson L.; Bell, Richard L.; Adams, Zachary W.; Hulvershorn, Leslie A. (Frontiers in Psychiatry, 2017)
Alcohol use, particularly binge drinking, is a major public health concern among adolescents. Recent national data show that the gender gap in alcohol use is lessening, and binge drinking among girls is rising. Considering the increase in binge drinking among adolescent girls, as well as females’ increased risk of experiencing more severe biopsychosocial negative effects and consequences from binge drinking, the current review sought to examine gender differences in risk factors for binge drinking. The review highlights gender differences in (1) developmental-related neurobiological vulnerability to binge drinking, (2) psychiatric comorbidity and risk phenotypes for binge drinking, and (3) social-related risk factors for binge drinking among adolescents, as well as considerations for binge drinking prevention and intervention. Most of the information gleaned thus far has come from preclinical research. However, it is expected that, with recent advances in clinical imaging technology, neurobiological effects observed in lower mammals will be confirmed in humans and vice versa. A synthesis of the literature highlights that males and females experience unique neurobiological paths of development, and although there is debate regarding the specific nature of these differences, literature suggests that these differences in turn influence gender differences in psychiatric comorbidity and risk for binge drinking. For one, girls are more susceptible to stress, depression, and other internalizing behaviors, and in turn, these symptoms contribute to their risk for binge drinking. On the other hand, males, given gender differences across the lifespan as well as gender differences in development, are driven by an externalizing phenotype for risk of binge drinking, in part, due to unique paths of neurobiological development that occur across adolescence. With respect to social domains, although social and peer influences are important for both adolescent males and females, there are gender differences. For example, girls may be more sensitive to pressure from peers to fit in and impress others, while male gender role stereotypes regarding binge drinking may be more of a risk factor for boys. Given these unique differences in male and female risk for binge drinking, further research exploring risk factors, as well as tailoring intervention and prevention, is necessary. Although